Development and validation of a method for simultaneous determination of trace levels of five macrocyclic lactones in cheese by HPLC-fluorescence after solid–liquid extraction with low temperature partitioning. (30th January 2019) - de Souza Santos Cheibub, Ana Maria; Silva Bahiense de Lyra, Eduardo; Pereira Netto, Annibal Duarte
Highlights: Five macrocyclic lactones were studied in cheese that is a very complex food matrix. An analytical method was developed and validated, following international guidelines. Excellent figures of merit were obtained with very low limits of quantification. Twenty-one of the twenty-two cheeses studied contained macrocyclic lactones. This is the first simultaneous evaluation of five macrocyclic lactones in cheeses. Abstract: A highly sensitive analytical method was developed and validated, following international guidelines, for the determination of the residues of five macrocyclic lactones (MLs) (abamectin, doramectin, eprinomectin, ivermectin and moxidectin) in cheese. The extracts were concentrated by rotary-evaporation and derivatized; no clean-up was necessary. Despite matrix complexity, no significant matrix-effect was verified, and standards were prepared in solvents. Linear working ranges varied from 0.25 to 5.0 μg L −1 . Excellent limits of quantification (0.58–0.87 μg kg −1 ), mean recoveries (91–103%), and repeatability and intermediate precision (<5.8%) were obtained. Twenty-two samples of bovine and non-bovine cheeses were analyzed. Twenty-one samples showed residues of at least one ML (between 0.59 and 15.3 μg kg −1 ), but moxidectin was never detected; a sample of mozzarella was free of MLs. To the best of our knowledge, this is the first method describing the simultaneous evaluation of these MLs in cheese using HPLC and fluorescence detection.